PECULIARITIES OF DEVELOPMENT OF CLASSICAL UNIVERSITIES IN EASTERN GERMANY - Gavryliuk, Anna V. (Educological discourse, 2015)
The article shows the peculiarities of development of German classical universities. The article concentrates on the main legislative documents that regulate the educational policy of Eastern Germany. It concentrates on the main tendencies of university education development in GDR. It also analyzes the development of the biggest and the oldest classical universities in Eastern Germany.